Tingkat Pengetahuan Orang Tua tentang Vaksinasi Covid-19 pada Anak Usia 6-11 Tahun di Kelurahan Bambu Kuning Kecamatan Tenayan Raya Pekanbaru - Norlita, Wiwik; Isnaniar; Setyani, Dwi (As-Shiha: Jurnal Kesehatan, 2023)
Parent’s knowledge about covid-19 vaccination in children aged 6-11 years is an important part in a series of efforts to overcome the Covid-19 pandemic in Indonesia with the main goal of vaccination at the age of 6-11 years for the formation of herd immunity, reducing the number and mortality due to Covid-19. This study aims to determine the level of knowledge of parents about covid-19 vaccination in children aged 6-11 years in Bambu Kuning sub-district Tenayan Raya Pekanbaru. The type of research used in this study is descriptive method. This research was conducted on June 29-July 28, 2022 in RW 12 Kelurahan Bambu Kuning, Tenayan Raya Pekanbaru District. The population in this study amounted to 185 parents who have children aged 6-11 years with a sample of respondents were 65 parents. The sampling technique used is Simple Random Sampling. The instrument used in this study is a questionnaire. The results showed that the description of the level of knowledge of parents about covid-19 vaccination in children aged 6-11 years in Bambu Kuning Sub-District Tenayan Raya Pekanbaru 27 respondents (41.5%) had good knowledge, 26 respondents (40.0%) were knowledgeable enough, while those with less knowledge were 12 respondents(18.5%). It can be concluded that the description of the level of knowledge of parents about covid-19 vaccination in children aged 6-11 years in RW 12 Kelurahan Bambu Kuning, Tenayan Raya Pekanbaru District is in the good category. It is expected that parents can improve their knowledge through health workers, books, electronic media by trusting actual and reliable information so that they can maintain and improve their good knowledge.